A New Method for Predicting Water Breakthrough Time in the Edge Water Condensate Gas Reservoir. Issue 1 (June 2020) - Huang, Quanhua; Lin, Xingyu; Xu, Qinglong; He, Yunjun
Abstract: The influence of condensate oil is often ignored when people predict the water breakthrough time of condensate gas reservoirs, leading to a certain difference between the prediction and the actual results. In order to efficiently and scientifically develop the edge water condensate gas reservoir, it is necessary to consider the influence of the precipitated condensate oil when making reasonable predictions on the water breakthrough time. Based on the basic law of gas-water two-phase percolation, this paper simplified the water inlet process as the migration of water particles to the well bottom, with the influence of condensate oil precipitation taken into consideration. In this meantime, this paper derived a new model for predicting the breakthrough time of the edge water condensate gas reservoir based on the idea that the change of condensate saturation varies with time and the distance from well bottom. Case studies show that the lower the permeability, the greater the influence of condensate oil precipitation on water breakthrough time; the farther the well bottom is from the initial gas-water boundary, the longer the water breakthrough time; the effect of condensate oil cannot be ignored during the prediction of the water breakthrough time in the edge water condensate gas reservoir. The new model considers the dual effects of time and location on the condensate saturation, which is more in line with the actual situation of the change of condensate saturation in the formation.